Pengaruh Postpurchase Price Perception dan Postpurchase Performance Perceptions Terhadap Satisfaction - Yudhiantoro, Danang (KINERJA, 2009)
University needs the trust from people with quality assurance, quality control, and quality improvement. The quality assurance and quality improvement can be doing with national accreditation. They need evaluation about customer satisfaction, from their perception about price, etc.Using linear regression with SPSS serial 16 to measure and explain the result from this concept, the overall impact of Postpurchase Price Perception and Postpurchase Performance Perception on satisfaction is positive. The implications of these findings for research, practice, and theory are discussed.